2015
DOI: 10.1007/s12282-015-0651-6
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcomes and technical considerations of nipple-sparing mastectomies in breast cancer: experience of 425 cases from a single institution

Abstract: NSM is safe with a low complication rate. No significant difference was observed in cumulative local recurrence rate, cumulative distant disease recurrence rate, and overall survival between patients who underwent NSM or conventional total mastectomy, confirming that NSM was surgically and oncologically safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…However, the indication of NSM is still under debate. Multiple studies have demonstrated that tumor size, tumor location, LN metastasis, lymphovascular invasion, histologic type, immunological characteristics like HER2 should be taken into consideration when propose NSM to breast cancer patients (14)(15)(16). In terms of LRR of NSM, none of our cases developed loco-regional or distant recurrence because of relative short follow-up time and highly selective cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the indication of NSM is still under debate. Multiple studies have demonstrated that tumor size, tumor location, LN metastasis, lymphovascular invasion, histologic type, immunological characteristics like HER2 should be taken into consideration when propose NSM to breast cancer patients (14)(15)(16). In terms of LRR of NSM, none of our cases developed loco-regional or distant recurrence because of relative short follow-up time and highly selective cases.…”
Section: Discussionmentioning
confidence: 99%
“…The mean follow-up time was 38 months (range, 7.4–156 months) and the overall LR rate was 2.38%. In recent years, studies have indicated that NSM was safe for oncology and led to similar LR and OS rates compared with those of patients treated with CM ( 18 , 34 ). These results were similar to those of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous prospective and retrospective studies, comprising patients with varying sample sizes, inclusion criteria and follow-up durations, have reported an LR rate of 0–24% following NSM ( 12 , 16 18 , 32 34 ). Although Benediktsson and Perbeck ( 33 ) reported a highest LR rate of 24% among these studies, the NAC recurrence rate was 4%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nipple sparing mastectomy (NSM) has been demonstrated to increase patient satisfaction and result in superior cosmetic outcomes compared to skin sparing mastectomy with nipple reconstruction (1,2). Over the past ten years, numerous studies have demonstrated NSM to be oncologically safe in appropriately selected patients and a viable alternative to skin-sparing mastectomy (3)(4)(5)(6). Based on the safety and efficacy of NSM and the possibility of aesthetic superiority, nipple preservation has become the preferred approach in the highest volume breast centers in the United States.…”
Section: Introductionmentioning
confidence: 99%